2021
DOI: 10.34172/apb.2022.043
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of Macromolecular Hydrogels for Enzyme Immobilization in the Food Products

Abstract: Enzymes are one of the main biocatalysts with various applications in the food industry. Stabilization of enzymes on insoluble carriers is important due to the low reuse, low operational stability, and high cost in applications. The immobility and the type of carrier affect the activity of the immobile enzyme. Hydrogels are three-dimensionally cross-linked macromolecular network structures designed from various polymers. Hydrogels can provide a matrix for an immobile enzyme due to their extraordinary propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…It has been reported that the stability of lipase can be enhanced by immobilizing lipase on octanyl agarose and octadecyl hydrogel beads by physical adsorption. [ 19 ]…”
Section: Design Of Enzyme‐based Biomaterials For Wound Treatmentmentioning
confidence: 99%
“…It has been reported that the stability of lipase can be enhanced by immobilizing lipase on octanyl agarose and octadecyl hydrogel beads by physical adsorption. [ 19 ]…”
Section: Design Of Enzyme‐based Biomaterials For Wound Treatmentmentioning
confidence: 99%
“…27 A large number of active functional groups in the hydrogel effectively increase the interaction between the enzyme molecules and the polymer framework of hydrogels, thereby improving the adhesion of enzymes and increasing the reuse efficiency of immobilized enzymes. 28,29 Although many kinds of hydrogel materials have been successfully applied to immobilize enzymes and significantly improve the value of enzymes in practical applications, the mechanism by which hydrogel properties affect specific enzymes and specific catalytic reactions is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A polyacrylamide (PAAm) conducting hydrogel has been widely used in sensors, electronic skins, and wearable devices due to its good biocompatibility and fast electron transfer capability. , The PAAm hydrogel has a chemically cross-linked three-dimensional network structure, a high permeability, and a hydrophilic property . More importantly, it has been utilized to achieve the effective immobilization of biomolecules and maintain their reactivity. , The hydrogel also has a good anti-fouling property and can inhibit the non-specific adsorption of non-target molecules on the surface of a sensor . Moreover, to our knowledge, the demonstration of a high-performance bioelectronic tongue integrating hydrogels with umami receptors for sensitive monitoring of umami substances has not been achieved.…”
mentioning
confidence: 99%
“…16 More importantly, it has been utilized to achieve the effective immobilization of biomolecules and maintain their reactivity. 17,18 The hydrogel also has a good anti-fouling property and can inhibit the non-specific adsorption of nontarget molecules on the surface of a sensor. 19 Moreover, to our knowledge, the demonstration of a high-performance bioelectronic tongue integrating hydrogels with umami receptors for sensitive monitoring of umami substances has not been achieved.…”
mentioning
confidence: 99%